Wide-temperature high-rate solid-state battery

CN122136436BActive Publication Date: 2026-10-23GUANGZHOU JICHU ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610121187.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-29
Publication Date
2026-10-23
Estimated Expiration
2046-01-29

AI Technical Summary

Technical Problem

现有的固态电池倍率和循环性能差,以及产品在高温-低温的宽温条件下,性能稳定性降低明显,限制了产品的使用效率,基于此,本发明对其进一步的改进处理

Benefits of technology

本发明固态电池采用正极片、负极片和固体电解质浆料组成,固体电解质浆料采用Li3PS4、丁腈橡胶和四氢呋喃配合,同时加入的改性二氧化钛剂、膨润土插层剂相互调和优化,改性二氧化钛剂采用二氧化钛经过改性液改进,改性液中的A改液配合B改剂共混球磨改进,A改液中的氧化硼、氧化锆调和十二烷基苯磺酸钠溶液和硅烷偶联剂KH550,B改剂采用金刚石粉经过氯化镧溶液和磷酸缓冲溶液改进优化,从而制成的改性二氧化钛剂在体系中增强产品的电池倍率和循环性能,以及产品在高温-低温的宽温条件下,性能稳定性优异;膨润土插层剂采用膨润土、石墨烯配合经过烧结改进,同时再通过球磨液球磨改进,球磨液中的二氧化硅、壳聚糖溶液和硼酸铝晶须以及Yb2O3调和优化,硼酸铝晶须以晶须结构配合,再配合二氧化硅和Yb2O3配合协调,从而球磨液球磨改进的膨润土插层剂与改性二氧化钛剂协配效果更好,进而产品的性能得到进一步的改进。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of wide temperature high rate solid-state battery, the solid-state battery includes positive pole piece, negative pole piece and solid electrolyte slurry;Wherein positive pole is positive pole material coated in aluminum foil piece dry formation;Negative pole is lithium piece;Solid electrolyte slurry is coated in positive pole piece and forms solid electrolyte layer, then negative pole piece is placed in solid electrolyte layer vacuum heating, obtains solid-state battery.Solid-state battery adopts positive pole piece, negative pole piece and solid electrolyte slurry composition, solid electrolyte slurry uses Li3PS, butyronitrile rubber and tetrahydrofuran cooperate, while adding modified titanium dioxide agent, bentonite intercalation agent each other harmonizes optimization, to be made into modified titanium dioxide agent in system strengthens the battery rate and cycle performance of product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state battery technology, and more specifically to a wide-temperature, high-rate solid-state battery. Background Technology

[0002] Lithium-ion batteries, characterized by high energy density, long cycle life, no memory effect, and no environmental pollution, have been widely used in portable electronic devices and electric vehicles. Therefore, lithium-ion batteries and related materials have become a hot research topic. Existing solid-state batteries suffer from poor rate capability and cycle performance, and their performance stability decreases significantly under wide temperature conditions (high to low), limiting their efficiency. Based on this, this invention provides further improvements. Summary of the Invention

[0003] In view of the shortcomings of the prior art, the purpose of this invention is to provide a wide-temperature, high-rate solid-state battery to solve the problems mentioned in the background art.

[0004] The present invention solves the technical problem by adopting the following technical solution: This invention provides a wide-temperature, high-rate solid-state battery, which includes a positive electrode, a negative electrode, and a solid electrolyte slurry; wherein the positive electrode is formed by coating a positive electrode material onto an aluminum foil and drying it; the negative electrode is a lithium sheet; the solid electrolyte slurry is coated onto the positive electrode to form a solid electrolyte layer, and then the negative electrode is placed in the solid electrolyte layer and heated under vacuum to obtain a solid-state battery; The preparation method of solid electrolyte slurry is as follows: Mix 10-15 parts Li3PS4, 3-5 parts nitrile rubber and 35-40 parts tetrahydrofuran evenly, then add 4-7 parts modified titanium dioxide and 3-5 parts bentonite intercalating agent, and continue to mix thoroughly to obtain a solid electrolyte slurry.

[0005] Preferably, the positive electrode material is prepared by dissolving titanium sulfide, an ion-conducting agent, and a binder in a solvent, wherein the ion-conducting agent is Li3PS4; the solvent is tetrahydrofuran; the binder is nitrile rubber; the mass ratio of titanium sulfide, ion-conducting agent, binder, and solvent is 3:5:2:25; and the vacuum heating is carried out at 180°C and a heating pressure of 20 MPa with a vacuum degree of 10. -3 MPa.

[0006] Preferably, the modified titanium dioxide agent is prepared by: S01: Preparation of the modified liquid: S01a: Add 2-4 parts of boron oxide and 2-3 parts of zirconium oxide to 5-8 parts of sodium dodecylbenzenesulfonate solution with a mass fraction of 5%, then add 1-2 parts of silane coupling agent KH550, mix evenly, and obtain modified solution A; S01b: Mix diamond powder with lanthanum chloride solution at 5-8 times the total weight of diamond powder, then add phosphate buffer solution at 10-15% of the total weight of diamond powder, continue mixing thoroughly, and finally filter and dry to obtain modifier B. Modifier B and modified liquid A were mixed and ball-milled at a weight ratio of 3:5. After ball milling, the modified liquid was obtained. S02: Titanium dioxide is first stirred thoroughly in a sufficient amount of 6% potassium permanganate solution, then washed with water, filtered and dried. The dried titanium dioxide and the modification solution are stirred and modified at a weight ratio of 5:(8-11). After stirring, the mixture is filtered and dried to obtain the modified titanium dioxide agent.

[0007] Preferably, the lanthanum chloride solution has a mass fraction of 2-5%; and the phosphate buffer solution has a pH of 5.5.

[0008] Preferably, the ball milling speed for the blending ball milling treatment is 1000-1500 r / min, and the ball milling time is 2 h; the stirring speed for the stirring modification treatment is 550-750 r / min, and the stirring time is 1 h.

[0009] Preferably, the preparation method of the bentonite intercalating agent is as follows: S11: Bentonite and graphene are mixed evenly at a weight ratio of 5:2, then sintered at 310-320℃ for 1 hour, and then cooled to 55℃ at a rate of 2-5℃ / min and held at that temperature. S12: The preparation method of the ball milling fluid is as follows: Mix 3-5 parts of silica, 5-8 parts of chitosan solution, 2-3 parts of aluminum borate whiskers and 1-2 parts of Yb2O3 evenly to obtain ball milling slurry; S11 treated bentonite and ball milling fluid were mixed and ball milled at a speed of 1200-1500 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain bentonite intercalating agent.

[0010] Preferably, the chitosan solution has a mass fraction of 2-5%.

[0011] Preferably, the mass ratio of bentonite and ball milling fluid treated in S11 is (7-11):5.

[0012] Preferably, the coating thickness of the positive electrode material on the aluminum foil is 80-100µm.

[0013] Compared with the prior art, the present invention has the following beneficial effects: This invention relates to a solid-state battery composed of a positive electrode, a negative electrode, and a solid electrolyte slurry. The solid electrolyte slurry is made from Li3PS4, nitrile rubber, and tetrahydrofuran, with modified titanium dioxide and bentonite intercalating agent added for mutual optimization. The modified titanium dioxide is obtained by modifying titanium dioxide with a modification solution. Modification solution A is blended with modification agent B and ball-milled for improvement. Modification solution A contains boron oxide, zirconium oxide, sodium dodecylbenzenesulfonate solution, and silane coupling agent KH550. Modification agent B is made from diamond powder modified and optimized with lanthanum chloride solution and phosphate buffer solution, thus producing a modified titanium dioxide slurry. Titanium oxide agents enhance the battery rate and cycle performance of the product in the system, and the product exhibits excellent performance stability under a wide temperature range of high and low temperatures. The bentonite intercalating agent is improved by sintering bentonite and graphene, and further improved by ball milling in ball milling slurry. The silica, chitosan solution, aluminum borate whiskers, and Yb2O3 in the ball milling slurry are blended and optimized. The aluminum borate whiskers are combined with the whisker structure, and then coordinated with silica and Yb2O3. Thus, the ball milling improved bentonite intercalating agent and modified titanium dioxide agent have a better synergistic effect, thereby further improving the performance of the product. Detailed Implementation

[0014] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0015] This embodiment provides a wide-temperature, high-rate solid-state battery, which includes a positive electrode, a negative electrode, and a solid electrolyte slurry. The positive electrode is formed by coating a positive electrode material onto an aluminum foil and drying it. The negative electrode is a lithium sheet. The solid electrolyte slurry is coated onto the positive electrode to form a solid electrolyte layer, and then the negative electrode is placed in the solid electrolyte layer and heated under vacuum to obtain the solid-state battery. The preparation method of solid electrolyte slurry is as follows: Mix 10-15 parts Li3PS4, 3-5 parts nitrile rubber and 35-40 parts tetrahydrofuran evenly, then add 4-7 parts modified titanium dioxide and 3-5 parts bentonite intercalating agent, and continue to mix thoroughly to obtain a solid electrolyte slurry.

[0016] In this embodiment, the positive electrode material is prepared by dissolving titanium sulfide, an ion-conducting agent, and a binder in a solvent. The ion-conducting agent is Li3PS4; the solvent is tetrahydrofuran; and the binder is nitrile rubber. The mass ratio of titanium sulfide, ion-conducting agent, binder, and solvent is 3:5:2:25. Vacuum heating is performed at 180°C and a heating pressure of 20 MPa, with a vacuum degree of 10. -3 MPa.

[0017] The preparation method of the modified titanium dioxide agent in this embodiment is as follows: S01: Preparation of the modified liquid: S01a: Add 2-4 parts of boron oxide and 2-3 parts of zirconium oxide to 5-8 parts of sodium dodecylbenzenesulfonate solution with a mass fraction of 5%, then add 1-2 parts of silane coupling agent KH550, mix evenly, and obtain modified solution A; S01b: Mix diamond powder with lanthanum chloride solution at 5-8 times the total weight of diamond powder, then add phosphate buffer solution at 10-15% of the total weight of diamond powder, continue mixing thoroughly, and finally filter and dry to obtain modifier B. Modifier B and modified liquid A were mixed and ball-milled at a weight ratio of 3:5. After ball milling, the modified liquid was obtained. S02: Titanium dioxide is first stirred thoroughly in a sufficient amount of 6% potassium permanganate solution, then washed with water, filtered and dried. The dried titanium dioxide and the modification solution are stirred and modified at a weight ratio of 5:(8-11). After stirring, the mixture is filtered and dried to obtain the modified titanium dioxide agent.

[0018] In this embodiment, the lanthanum chloride solution has a mass fraction of 2-5%; the phosphate buffer solution has a pH value of 5.5.

[0019] In this embodiment, the ball milling speed for the blending ball milling treatment is 1000-1500 r / min, and the ball milling time is 2 h; the stirring speed for the stirring modification treatment is 550-750 r / min, and the stirring time is 1 h.

[0020] The preparation method of the bentonite intercalating agent in this embodiment is as follows: S11: Bentonite and graphene are mixed evenly at a weight ratio of 5:2, then sintered at 310-320℃ for 1 hour, and then cooled to 55℃ at a rate of 2-5℃ / min and held at that temperature. S12: The preparation method of the ball milling fluid is as follows: Mix 3-5 parts of silica, 5-8 parts of chitosan solution, 2-3 parts of aluminum borate whiskers and 1-2 parts of Yb2O3 evenly to obtain ball milling slurry; S11 treated bentonite and ball milling fluid were mixed and ball milled at a speed of 1200-1500 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain bentonite intercalating agent.

[0021] The chitosan solution in this embodiment has a mass fraction of 2-5%.

[0022] In this embodiment, the mass ratio of bentonite and ball milling fluid treated by S11 is (7-11):5.

[0023] In this embodiment, the positive electrode material is coated on the aluminum foil with a thickness of 80-100µm.

[0024] Example 1. This embodiment provides a wide-temperature, high-rate solid-state battery, which includes a positive electrode, a negative electrode, and a solid electrolyte slurry. The positive electrode is formed by coating a positive electrode material onto an aluminum foil and drying it. The negative electrode is a lithium sheet. The solid electrolyte slurry is coated onto the positive electrode to form a solid electrolyte layer, and then the negative electrode is placed in the solid electrolyte layer and heated under vacuum to obtain the solid-state battery. The preparation method of solid electrolyte slurry is as follows: 10 parts Li3PS4, 3 parts nitrile rubber and 35 parts tetrahydrofuran were mixed evenly, and then 4 parts modified titanium dioxide and 3 parts bentonite intercalating agent were added and mixed thoroughly to obtain a solid electrolyte slurry.

[0025] In this embodiment, the positive electrode material is prepared by dissolving titanium sulfide, an ion-conducting agent, and a binder in a solvent. The ion-conducting agent is Li3PS4; the solvent is tetrahydrofuran; and the binder is nitrile rubber. The mass ratio of titanium sulfide, ion-conducting agent, binder, and solvent is 3:5:2:25. Vacuum heating is performed at 180°C and a heating pressure of 20 MPa, with a vacuum degree of 10. -3 MPa.

[0026] The preparation method of the modified titanium dioxide agent in this embodiment is as follows: S01: Preparation of the modified liquid: S01a: Add 2 parts boron oxide and 2 parts zirconium oxide to 5 parts sodium dodecylbenzenesulfonate solution with a mass fraction of 5%, then add 1 part silane coupling agent KH550, mix evenly, and obtain modified solution A; S01b: Diamond powder is stirred evenly in a lanthanum chloride solution that is 5 times the total weight of diamond powder. Then, 10% of the total weight of diamond powder in phosphate buffer solution is added and mixed thoroughly. Finally, the mixture is filtered and dried to obtain modifier B. Modifier B and modified liquid A were mixed and ball-milled at a weight ratio of 3:5. After ball milling, the modified liquid was obtained. S02: Titanium dioxide is first stirred thoroughly in a sufficient amount of 6% potassium permanganate solution, then washed with water, filtered, and dried. The dried titanium dioxide and the modification solution are stirred at a weight ratio of 5:8 for modification treatment. After stirring, the mixture is filtered and dried to obtain the modified titanium dioxide agent.

[0027] In this embodiment, the lanthanum chloride solution has a mass fraction of 2%; the phosphate buffer solution has a pH value of 5.5.

[0028] In this embodiment, the ball milling speed for the blending ball milling treatment is 1000 r / min, and the ball milling time is 2 h; the stirring speed for the stirring modification treatment is 550 r / min, and the stirring time is 1 h.

[0029] The preparation method of the bentonite intercalating agent in this embodiment is as follows: S11: Bentonite and graphene are mixed evenly at a weight ratio of 5:2, then sintered at 310℃ for 1 hour, and then cooled to 55℃ at a rate of 2℃ / min and kept warm. S12: The preparation method of the ball milling fluid is as follows: 3 parts silica, 5 parts chitosan solution, 2 parts aluminum borate whiskers and 1 part Yb2O3 were mixed evenly to obtain a ball milling slurry; S11 treated bentonite and ball milling fluid were mixed and ball milled at a speed of 1200 r / min for 2 h. After ball milling, the mixture was filtered and dried to obtain bentonite intercalating agent.

[0030] The chitosan solution in this embodiment has a mass fraction of 2%.

[0031] In this embodiment, the mass ratio of bentonite to ball milling fluid in the S11 treatment is 7:5.

[0032] In this embodiment, the positive electrode material is coated on the aluminum foil with a coating thickness of 80µm.

[0033] Example 2

[0034] This embodiment provides a wide-temperature, high-rate solid-state battery, which includes a positive electrode, a negative electrode, and a solid electrolyte slurry. The positive electrode is formed by coating a positive electrode material onto an aluminum foil and drying it. The negative electrode is a lithium sheet. The solid electrolyte slurry is coated onto the positive electrode to form a solid electrolyte layer, and then the negative electrode is placed in the solid electrolyte layer and heated under vacuum to obtain the solid-state battery. The preparation method of solid electrolyte slurry is as follows: 15 parts Li3PS4, 5 parts nitrile rubber and 40 parts tetrahydrofuran were mixed evenly, and then 7 parts modified titanium dioxide and 5 parts bentonite intercalating agent were added and mixed thoroughly to obtain a solid electrolyte slurry.

[0035] In this embodiment, the positive electrode material is prepared by dissolving titanium sulfide, an ion-conducting agent, and a binder in a solvent. The ion-conducting agent is Li3PS4; the solvent is tetrahydrofuran; and the binder is nitrile rubber. The mass ratio of titanium sulfide, ion-conducting agent, binder, and solvent is 3:5:2:25. Vacuum heating is performed at 180°C and a heating pressure of 20 MPa, with a vacuum degree of 10. -3 MPa.

[0036] The preparation method of the modified titanium dioxide agent in this embodiment is as follows: S01: Preparation of the modified liquid: S01a: Add 4 parts boron oxide and 3 parts zirconium oxide to -8 parts sodium dodecylbenzenesulfonate solution with a mass fraction of 5%, then add 2 parts silane coupling agent KH550, mix evenly, and obtain modified solution A; S01b: Diamond powder is stirred evenly in a lanthanum chloride solution with a volume of 8 times the total volume of diamond powder. Then, 15% of the total volume of diamond powder in phosphate buffer solution is added and mixed thoroughly. Finally, the mixture is filtered and dried to obtain modifier B. Modifier B and modified liquid A were mixed and ball-milled at a weight ratio of 3:5. After ball milling, the modified liquid was obtained. S02: Titanium dioxide is first stirred thoroughly in a sufficient amount of 6% potassium permanganate solution, then washed with water, filtered, and dried. The dried titanium dioxide and the modification solution are stirred at a weight ratio of 5:11 for modification treatment. After stirring, the mixture is filtered and dried to obtain the modified titanium dioxide agent.

[0037] In this embodiment, the lanthanum chloride solution has a mass fraction of 5%; the phosphate buffer solution has a pH value of 5.5.

[0038] In this embodiment, the ball milling speed for the blending ball milling treatment is 1500 r / min, and the ball milling time is 2 h; the stirring speed for the stirring modification treatment is 750 r / min, and the stirring time is 1 h.

[0039] The preparation method of the bentonite intercalating agent in this embodiment is as follows: S11: Bentonite and graphene are mixed evenly at a weight ratio of 5:2, then sintered at 320℃ for 1 hour, and then cooled to 55℃ at a rate of 5℃ / min and kept warm. S12: The preparation method of the ball milling fluid is as follows: 5 parts silica, 8 parts chitosan solution, 3 parts aluminum borate whiskers and 2 parts Yb2O3 were mixed evenly to obtain a ball milling slurry; S11 treated bentonite and ball milling fluid were mixed and ball milled at a speed of 1500 r / min for 2 h. After ball milling, the mixture was filtered and dried to obtain bentonite intercalating agent.

[0040] The chitosan solution in this embodiment has a mass fraction of 5%.

[0041] In this embodiment, the mass ratio of bentonite to ball milling fluid in the S11 treatment is 11:5.

[0042] In this embodiment, the positive electrode material is coated on the aluminum foil with a thickness of 100µm.

[0043] Example 3. This embodiment provides a wide-temperature, high-rate solid-state battery, which includes a positive electrode, a negative electrode, and a solid electrolyte slurry. The positive electrode is formed by coating a positive electrode material onto an aluminum foil and drying it. The negative electrode is a lithium sheet. The solid electrolyte slurry is coated onto the positive electrode to form a solid electrolyte layer, and then the negative electrode is placed in the solid electrolyte layer and heated under vacuum to obtain the solid-state battery. The preparation method of solid electrolyte slurry is as follows: 12.5 parts Li3PS4, 4 parts nitrile rubber and 37.5 parts tetrahydrofuran were mixed evenly, and then 5.5 parts modified titanium dioxide and 4 parts bentonite intercalating agent were added and mixed thoroughly to obtain a solid electrolyte slurry.

[0044] In this embodiment, the positive electrode material is prepared by dissolving titanium sulfide, an ion-conducting agent, and a binder in a solvent. The ion-conducting agent is Li3PS4; the solvent is tetrahydrofuran; and the binder is nitrile rubber. The mass ratio of titanium sulfide, ion-conducting agent, binder, and solvent is 3:5:2:25. Vacuum heating is performed at 180°C and a heating pressure of 20 MPa, with a vacuum degree of 10. -3 MPa.

[0045] The preparation method of the modified titanium dioxide agent in this embodiment is as follows: S01: Preparation of the modified liquid: S01a: Add 3 parts boron oxide and 2.5 parts zirconium oxide to 6.5 parts sodium dodecylbenzenesulfonate solution with a mass fraction of 5%, then add 1.5 parts silane coupling agent KH550 and mix evenly to obtain modified solution A; S01b: Diamond powder is stirred evenly in a lanthanum chloride solution with a volume of 6.5 times the total volume of diamond powder. Then, a phosphate buffer solution with a volume of 12.5% ​​of the total volume of diamond powder is added and mixed thoroughly. Finally, the mixture is filtered and dried to obtain modifier B. Modifier B and modified liquid A were mixed and ball-milled at a weight ratio of 3:5. After ball milling, the modified liquid was obtained. S02: Titanium dioxide is first stirred thoroughly in a sufficient amount of 6% potassium permanganate solution, then washed with water, filtered, and dried. The dried titanium dioxide and the modification solution are stirred and modified at a weight ratio of 5:9.5. After stirring, the mixture is filtered and dried to obtain the modified titanium dioxide agent.

[0046] In this embodiment, the lanthanum chloride solution has a mass fraction of 3.5%; the phosphate buffer solution has a pH value of 5.5.

[0047] In this embodiment, the ball milling speed for the blending ball milling treatment is 1250 r / min, and the ball milling time is 2 h; the stirring speed for the stirring modification treatment is 600 r / min, and the stirring time is 1 h.

[0048] The preparation method of the bentonite intercalating agent in this embodiment is as follows: S11: Bentonite and graphene are mixed evenly at a weight ratio of 5:2, then sintered at 315℃ for 1 hour, and then cooled to 55℃ at a rate of 3.5℃ / min and held at that temperature. S12: The preparation method of the ball milling fluid is as follows: Four parts of silica, 6.5 parts of chitosan solution, 2.5 parts of aluminum borate whiskers, and 1.5 parts of Yb2O3 were mixed evenly to obtain a ball milling slurry. S11 treated bentonite and ball milling fluid were mixed and ball milled at a speed of 1350 r / min for 2 h. After ball milling, the mixture was filtered and dried to obtain bentonite intercalating agent.

[0049] The chitosan solution in this embodiment has a mass fraction of 3.5%.

[0050] In this embodiment, the mass ratio of bentonite and ball milling fluid treated in S11 is 8.5:5.

[0051] In this embodiment, the positive electrode material is coated on the aluminum foil with a coating thickness of 90µm.

[0052] Comparative Example 1. Unlike Example 3, no modified titanium dioxide was added.

[0053] Comparative Example 2. Unlike Example 3, no modifying liquid treatment was used in the preparation of the modified titanium dioxide agent.

[0054] Comparative Example 3. Unlike Example 3, no modifier B was added to the modified liquid.

[0055] Comparative Example 4. Unlike Example 3, Boron oxide and Zirconium oxide were not added to Modifier B.

[0056] Comparative Example 5. Unlike Example 3, no modified solution A was added to the modified solution.

[0057] Comparative Example 6. Unlike Example 3, no bentonite intercalating agent was added.

[0058] Comparative Example 7. Unlike Example 3, no ball milling fluid was added during the preparation of the bentonite intercalating agent.

[0059] Comparative Example 8. Unlike Example 3, aluminum borate whiskers and Yb2O3 were not added to the ball milling slurry.

[0060] The product performance tests of Examples 1-3 and Comparative Examples 1-8 were conducted, and the test results are as follows:

[0061] As can be seen from Examples 1-3 and Comparative Examples 1-8, the product of the present invention can achieve high rate capability, high cycle life, and wide temperature stability. The product's performance deteriorates significantly if either modified titanium dioxide or bentonite intercalating agent is not added. By combining the two in combination, the product's performance is most significantly enhanced. In the preparation of modified titanium dioxide, no modifying liquid treatment was used, no B modifier was added to the modifying liquid, no boron oxide or zirconium oxide was added to the B modifier, and no A modifier was added to the modifying liquid. In the preparation of bentonite intercalating agent, no ball milling slurry was added, and no aluminum borate whiskers or Yb2O3 were added to the ball milling slurry. The performance of the products all tended to deteriorate. Only when the bentonite intercalating agent obtained by the method of this invention is combined with the modified titanium dioxide obtained by the specific method of this invention, the performance of the product is most significant. Using other methods to replace it is not as effective as the results of this invention.

[0062] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0063] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A wide-temperature, high-rate solid-state battery, characterized in that, The solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte slurry; wherein the positive electrode is formed by coating a positive electrode material onto an aluminum foil sheet and drying it; the negative electrode is a lithium sheet; the solid electrolyte slurry is coated onto the positive electrode to form a solid electrolyte layer, and then the negative electrode is placed on the solid electrolyte layer and heated under vacuum to obtain a solid-state battery; The preparation method of solid electrolyte slurry is as follows: Mix 10-15 parts of Li3PS4, 3-5 parts of nitrile rubber and 35-40 parts of tetrahydrofuran evenly, then add 4-7 parts of modified titanium dioxide and 3-5 parts of bentonite intercalating agent, and continue to mix thoroughly to obtain a solid electrolyte slurry. The preparation method of the modified titanium dioxide agent is as follows: S01: Preparation of the modified liquid: S01a: Add 2-4 parts of boron oxide and 2-3 parts of zirconium oxide to 5-8 parts of sodium dodecylbenzenesulfonate solution with a mass fraction of 5%, then add 1-2 parts of silane coupling agent KH550, mix evenly, and obtain modified solution A; S01b: Mix diamond powder with lanthanum chloride solution at 5-8 times the total weight of diamond powder, then add phosphate buffer solution at 10-15% of the total weight of diamond powder, continue mixing thoroughly, and finally filter and dry to obtain modifier B. Modifier B and modified liquid A were mixed and ball-milled at a weight ratio of 3:

5. After ball milling, the modified liquid was obtained. S02: Titanium dioxide is first stirred thoroughly in a sufficient amount of 6% potassium permanganate solution, then washed with water, filtered and dried. The dried titanium dioxide and the modification solution are stirred and modified at a weight ratio of 5:(8-11). After stirring, the mixture is filtered and dried to obtain the modified titanium dioxide agent. The lanthanum chloride solution has a mass fraction of 2-5%; the phosphate buffer solution has a pH of 5.5; and the bentonite intercalating agent is prepared as follows: S11: Bentonite and graphene are mixed evenly at a weight ratio of 5:2, then sintered at 310-320℃ for 1 hour, and then cooled to 55℃ at a rate of 2-5℃ / min and held at that temperature. S12: The preparation method of the ball milling fluid is as follows: Mix 3-5 parts of silica, 5-8 parts of chitosan solution, 2-3 parts of aluminum borate whiskers and 1-2 parts of Yb2O3 evenly to obtain ball milling slurry; S11 treated bentonite and ball milling fluid were mixed and ball milled at a speed of 1200-1500 r / min for 2 hours. After ball milling, the mixture was filtered and dried to obtain bentonite intercalating agent.

2. The wide-temperature, high-rate solid-state battery according to claim 1, characterized in that, The positive electrode material is prepared by dissolving titanium sulfide, an ion-conducting agent, and a binder in a solvent. The ion-conducting agent is Li3PS4; the solvent is tetrahydrofuran; and the binder is nitrile rubber. The mass ratio of titanium sulfide, ion-conducting agent, binder, and solvent is 3:5:2:

25. Vacuum heating is performed at 180°C and a heating pressure of 20 MPa, with a vacuum degree of 10. -3 MPa.

3. A wide-temperature, high-rate solid-state battery according to claim 1, characterized in that, The ball milling speed for the blending ball milling treatment is 1000-1500 r / min, and the ball milling time is 2 h; the stirring speed for the stirring modification treatment is 550-750 r / min, and the stirring time is 1 h.

4. A wide-temperature, high-rate solid-state battery according to claim 1, characterized in that, The chitosan solution has a mass fraction of 2-5%.

5. A wide-temperature, high-rate solid-state battery according to claim 1, characterized in that, The mass ratio of bentonite and ball milling fluid treated in S11 is (7-11):

5.

6. A wide-temperature, high-rate solid-state battery according to claim 1, characterized in that, The positive electrode material is coated on the aluminum foil with a thickness of 80-100µm.

Citation Information

Patent Citations

  • Isolating membrane, battery monomer, battery and electric device

    CN120261901A

  • All-solid-state energy storage device and method for manufacturing all-solid-state energy storage device

    EP4625519A1